Development of Indau Seed Technology (Eruca Sativa Mill) in the Southern Region of Uzbekistan - Muqimov B.B; Aramov M.Kh (Periodica Journal, 2022)
The article presents the results of research on the development of elements of seed production technology introduced in the conditions of Uzbekistan, a rare, but valuable in terms of nutritional values and medicinal properties of a vegetable crop - indau. The largest and high-quality seed yield (4.5-5.5 t/ha) was obtained when seeds were sown on September 10 and the planting pattern was 70x20 cm, 70x25 cm. Studies have shown high seed productivity and high efficiency of indau seed production in Uzbekistan
Keywords: planting; height; number; seeds